STRESS ON COLLEGE STUDENTS WHO DO MERANTAU - Mahargyantari Purwani Dewi (Universitas Gunadarma, 2008)
Merantau is activity when someone is leaving his/her residence area to the other are that far from his/her residence area. Many college students is far from their residence area for study. In their daily activities, there are many problems that have to be faced because the differentiation of their own culture and at the end it creates stress. The aim of this study is to gain the description about stres that felt by the college students who go far from their own residence area for study. Participant of this study is a female college student. The result shows that stress symptoms happened to the participant area sleep problem, mood problem, and skin problem. The academic stressors are transportation problem, adaptation problem, the task from lecturers, and the use of college facilities. The family problems are about health and her little boy. The economic stressor is about living alowences. And, the environmental stresso are about socialization and adaptation problems in the neighbourhood. Key words: stress, merantau, college students